72=3(-5n-1)

Simple and best practice solution for 72=3(-5n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72=3(-5n-1) equation:


Simplifying
72 = 3(-5n + -1)

Reorder the terms:
72 = 3(-1 + -5n)
72 = (-1 * 3 + -5n * 3)
72 = (-3 + -15n)

Solving
72 = -3 + -15n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '15n' to each side of the equation.
72 + 15n = -3 + -15n + 15n

Combine like terms: -15n + 15n = 0
72 + 15n = -3 + 0
72 + 15n = -3

Add '-72' to each side of the equation.
72 + -72 + 15n = -3 + -72

Combine like terms: 72 + -72 = 0
0 + 15n = -3 + -72
15n = -3 + -72

Combine like terms: -3 + -72 = -75
15n = -75

Divide each side by '15'.
n = -5

Simplifying
n = -5

See similar equations:

| 0.66666666666x-2=7 | | 2cos(2x-y)dx-cos(2x-y)dy=0 | | 9.8*7.9= | | 5x*(x+50)=29950 | | 21+7=31.64 | | 3p-7=-(p-4) | | 100=-4(6x-1) | | 5x-12=8-2x | | x^2-8+1=10 | | 3p+7=-(p-4) | | -90=5(2-5p) | | .05((1-x^6)/(1-x))=100 | | 24uv^4w^7-28u^4v^8=0 | | (1/6,-2) | | (3m+2n-7p)=-6m^3np^3-4m^2n^2p^3+14m^2np^4 | | 6x^3=729 | | 2(x+4)-2=4(x+2)-6 | | 50x^2-5x-3= | | 18x-3x=10 | | -10(s+1)=-71 | | 2/3a-4=4 | | 7c+2=5c-10 | | (x+2y)+(2x-3y)i+4i=5 | | (2x^2-3x+6)=-8x^3-24x^2 | | 3x=ax+1 | | (x+2)+(2x-3y)i+4i=5 | | 4/5f=2/3 | | 6(3s+4)=96 | | (2x+3(x-7))=0 | | 0.25e=8 | | 5(a-6)=75 | | -2(z+4)=44 |

Equations solver categories